Pengaruh Pembiasaan Tadarus Al-Qur’an Terhadap Terbentuknya Karakter Religius Siswa Kelas XI Di SMAN 1 Kota Bogor - Santi Lisnawati; Riva Farisha (CV. ITTC INDONESIA, 2025)
The world of education has many goals to be achieved, one of which is to foster religious character and develop good character in students. By habituating the recitation of the Qur'an in schools, students should be able to understand and form a religious character in themselves. This study aims to determine the level of habituation of the recitation of the Qur'an of class XI students at SMAN 1 Bogor City, to determine the level of religious character of class XI students at SMAN 1 Bogor City and to determine whether there is an influence of the habituation of the recitation of the Qur'an on the religious character of class XI students at SMAN 1 Bogor City. The research method used in this study is quantitative research. This study used a population of all eleventh-grade students at SMAN 1 Bogor City, with a sample of 159 students drawn randomly. The instruments used in this study were questionnaires and documentation. The data analysis technique used simple linear regression analysis with the help of SPSS 20 application.The results of the study show that: First, the habit of Al-Qur'an recitation of grade XI students at SMAN 1 Bogor City obtained a value in the